2023
DOI: 10.1017/jfm.2023.131
|View full text |Cite
|
Sign up to set email alerts
|

Two-way coupled long-wave isentropic ocean-atmosphere dynamics

Abstract: The events following the 15 January 2022 explosions of the Hunga Tonga-Hunga Ha'apai volcano highlighted the need for a better understanding of ocean-atmosphere interactions when large amounts of energy are locally injected into one (or both). Starting from the compressible Euler equations, a two-way coupled (TWC) system is derived governing the long-wave behaviour of the ocean and atmosphere under isentropic constraint. Bathymetry and topography are accounted for along with three-dimensional atmospheric non-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…The analysis of 1-min GOES-16 regional observations reveal the presence of fluctuations of much smaller scales than reported earlier based on 10-min imagery (Winn et al, 2023;Wright et al, 2022). Our results are in agreement with Horvath et al ( 2023) who suggested similar wavelengths and periods of fluctuations over CONUS and we refer to their study for the detailed analysis of 1-min GOES satellite observations over different mesoscale regions.…”
Section: Spatial and Temporal Evolution Of Agws And Tidssupporting
confidence: 92%
“…The analysis of 1-min GOES-16 regional observations reveal the presence of fluctuations of much smaller scales than reported earlier based on 10-min imagery (Winn et al, 2023;Wright et al, 2022). Our results are in agreement with Horvath et al ( 2023) who suggested similar wavelengths and periods of fluctuations over CONUS and we refer to their study for the detailed analysis of 1-min GOES satellite observations over different mesoscale regions.…”
Section: Spatial and Temporal Evolution Of Agws And Tidssupporting
confidence: 92%
“…The global propagation of this broad far-field atmospheric pressure pulse was well reproduced by Amores et al (2022), who introduced an instantaneous sea level perturbation in a shallow water ocean model as well as by Watanabe et al (2022), who imposed an instantaneous hot anomaly over the volcano in an atmospheric general circulation model. The atmospheric Lamb wave triggered a meteotsunami, the accurate numerical simulation of which also required the imposition of such long-period and long-wavelength pressure pulses as forcing (Heinrich et al, 2023;Kubota et al, 2022;Suzuki et al, 2023;Winn et al, 2023;Yamada et al, 2022).…”
Section: The Surface Pressure Waveformmentioning
confidence: 99%
“…Several studies tracked the global propagation of the primary Lamb wave emitted by HTHH using infrared brightness temperatures from geostationary satellites (Amores et al, 2022;Matoza et al, 2022;Otsuka, 2022;Winn et al, 2023). All of these studies used full disk (FD) imagery available either at 10-min cadence from the Advanced Baseline Imager (ABI) aboard the Geostationary Operational Environmental Satellite-R series (GOES-R) and the Advanced Himawari Imager (AHI) aboard the Himawari-8 satellite or at 15-min cadence from the Spinning Enhanced Visible and Infrared Imager (SEVIRI) aboard the Meteosat Second Generation satellites.…”
mentioning
confidence: 99%
See 2 more Smart Citations